Structure evolution and electrical properties of lead-free Bi0.5Na0.41K0.09TiO3 piezoceramics by isovalent La doping - Tran, Vu Diem Ngoc (Journal of Materials Science: Materials in Electronics, 2021)
This study investigated the structure evolution, surface morphology, dielectric properties, ferroelectric properties, piezoelectric properties, and electromechanical strain properties of lead-free (Bi0.5−xLax)(Na0.41K0.09)TiO3 piezoelectric ceramics. All samples were fabricated by a traditional solid-state synthesis. The effects of La3+-isovalent substituted on Bi3+-site of the Bi0.5Na0.41K0.09TiO3 system were examined. The addition of La doping in the Bi0.5Na0.41K0.09TiO3 ceramics induced the second phase of K4Ti3O8 and a crystal structural change from the rhombohedral and tetragonal phase to a pseudocubic phase. All samples show similar grain morphology and dense microstructure with the average grain size around 1.33 to 1.61 μm. The dielectric curves and field-induced polarization loops of samples confirm the nonergodic-to-ergodic relaxor phase transformation, corresponding to the reduction of the temperature at the phase transition from ferroelectric to relaxor phase and the disruption of the ferroelectric properties happened in samples when increasing La3+ content. Besides, the maximum piezoelectric constant of 139 pC/N was found in (Bi0.48La0.02)(Na0.41K0.09)TiO3 ceramic, while the (Bi0.46La0.04)(Na0.41K0.09)TiO3 ceramic shows a maximum strain of ~ 0.2% at a low field of 40 kV/cm.